Therapeutic application of retinoic acid-loaded nanoparticles for neurological and vascular repair in stroke - Fonseca, Márcia Carvalho da (2015)
In Portugal, stroke is the main cause of mortality and disability causing a substantial socioeconomic burden. However, available treatments only benefit a small percentage of patients and can cause serious side effects. The main aim of this project is to develop a new therapy for stroke that recovers the brain vasculature and induces survival and differentiation of neural stem cells. Thus, this work focuses on inducing a favorable pro-angiogenic environment for the vasculature to recover and to support neuronal and functional repair. This project proposes the use of retinoic acid-loaded nanoparticles as the therapeutic agent. Retinoic acid regulates vascular function and can increase endogenous neurogenesis. This formulation bypasses the limitations of free retinoic acid: low solubility and fast degradation thereby allowing retinoic acid to reach its full potential. Thus, the objectives of the project were: 1) to determine the modulatory role of retinoic acid-loaded nanoparticles on endothelial cell activity after being subjected to an in vitro model of oxygen/glucose deprivation to mimic the ischemic condition; 2) to define the role of endothelial cells treated with retinoic acid-loaded nanoparticles in the secretion of factors that promote the survival, repair and differentiation of neural stem cells. Retinoic acid-loaded nanoparticles treatment protected endothelial cells from ischemic injury, and in these experimental settings, retinoic acid-loaded nanoparticles-treated ischemic endothelial cells released factors that induced the survival, proliferation and differentiation of neural stem cells. Additionally, the results obtained with retinoic acid-loaded nanoparticles treatment showed increased efficiency (~83-fold higher) when compared to free retinoic acid treatment (not encapsulated). With these results in mind, retinoic acid-loaded nanoparticles demonstrated a relevant therapeutic potential for the treatment of stroke and possibly other vascular/neurodegenerative diseases.